Treatments of residual pine strands: characterization and wood-cement-compatibility - Cabral, Matheus R.; Nakanishi, Erika Y.; Franco, Mayara S. R.; Santos, Sérgio F. [UNESP]; Fiorelli, Juliano (Taylor & Francis, 2020)
This paper aims to evaluate treatments on pine strands as well as wood-cement compatibility. The strands were prepared and then were submitted to four treatments (untreated; cold water, hot water and NaOH). Physical, chemical, thermal and mechanical properties of the strands were measured. Wood-cement composites were produced with all strand treatments. To evaluate the strand effects on the cement hydration, axial compression tests were conducted at 28-day. The phases of the matrix of the composites at 24 h 7- and 28-day were also determinate. Fourier transform infrared spectra shows that, although the treatments partially removed the hemicellulose and extractives, they also reduced the cellulose and lignin bands. Axial compression results indicated that there were no differences between values for the composites with untreated and treated strands. For the phase analyses, in the initial ages (24 h and 7-day), it was identified that portlandite for cement sample (control) is higher than those containing the strands. At 28-day, it was found that among the strands, the untreated have the lower portlandite content and the higher calcium carbonate content. Indicating the cement carbonation over time as presented in the cement sample (control). Therefore, the untreated pine residual strand showed good compatibility with cement and for this study there were no benefits on treating the strands.
Keywords: cement materials; chemical treatment; composites; strand; Wood